Utilization of multiple SAVI SCOUT surgical guidance system reflectors in the same breast: A single‐institution feasibility study. Issue 4 (18th December 2017) - Jadeja, Priya H.; Mango, Victoria; Patel, Sejal; Friedlander, Lauren; Desperito, Elise; Ayala‐Bustamante, Everick; Wynn, Ralph; Chen‐Seetoo, Margaret; Taback, Bret; Feldman, Sheldon; Ha, Richard
Abstract: SAVI SCOUT Surgical Guidance System has been shown to be a reliable and safe alternative to wire localization in breast surgery. This study evaluated the feasibility of using multiple reflectors in the same breast. We performed an IRB‐approved, HIPAA‐compliant, single‐institution retrospective review of 183 patients who underwent breast lesion localization and excision using SAVI SCOUT Surgical Guidance System (Cianna Medical) between June 2015 and January 2017. We performed a subset analysis in 42 patients in whom more than one reflector was placed. Specimen radiography, pathology, distance between reflectors, target removal, margin positivity, and complications were evaluated. Among 183 patients, 42 patients had more than one reflector placed in the same breast to localize 68 lesions. Benign (n = 6, 8.8%), high‐risk (n = 23, 33.8%), and malignant (n = 39, 57.4%) lesions were included. Thirty‐six patients (85.7%) had a total of 2 reflectors placed and 6 patients had a total of 3 reflectors placed (14.3%). The indications for multiple reflector placement in the same breast included multiple separate lesions (n = 23) and bracketing of large lesions (n = 19). The mean distance between the reflectors was 42 mm (22‐93 mm). All lesions were successfully targeted and retrieved. Of 39 malignant lesions, 10.3% (n = 4) had positive margins and 10.3% (n = 4) had close (<1 mm) margins at surgery. All patients with positive margins underwent re‐excision. No complications occurred preoperatively, intra‐operatively, or postoperatively. The use of multiple SAVI SCOUT reflectors for localizing multiple lesions in the same breast or bracketing large lesions is feasible and safe.